2015
DOI: 10.1002/2015gc005880
|View full text |Cite
|
Sign up to set email alerts
|

A 1400 year environmental magnetic record from varved sediments of Lake Xiaolongwan (Northeast China) reflecting natural and anthropogenic soil erosion

Abstract: Lake sediments can provide high-quality information about human activities. In this study, we investigate a sediment core from Lake Xiaolongwan using magnetic and geochemical methods. The dominant magnetic minerals of this sediment core are stable single domain (SSD) and superparamagnetic (SP) magnetite particles. The increasing amount of SP particles reflected by the rise of magnetic susceptibility and frequency dependent magnetic susceptibility since AD 1500 can be attributed to an increasing influx in pedog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In recent years, studies have suggested that human activities play an important role in controlling ecosystems and soil erosion in monsoonal China. Increases in χ lf and χ fd over the last 2000 years in sediments from the Yangtze delta in eastern China, Lake Xiaolongwan in northeast China, and lakes Erhai and Xingyun in southwest China reflect an increase in soil erosion attributed to enhanced human activity (Dearing et al, 2008;Wang et al, 2010;Su et al, 2015;Wu et al, 2015). Numerous studies likewise found that increasing contents of various metals, including Cu, Pb, and Zn, could be closely linked to mining and metalworking activities, reflecting a progressive intensification of human activities (Zong et al, 2010;Hu et al, 2013;Hillman et al, 2014;Wan et al, 2015;Xu et al, 2017;Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies have suggested that human activities play an important role in controlling ecosystems and soil erosion in monsoonal China. Increases in χ lf and χ fd over the last 2000 years in sediments from the Yangtze delta in eastern China, Lake Xiaolongwan in northeast China, and lakes Erhai and Xingyun in southwest China reflect an increase in soil erosion attributed to enhanced human activity (Dearing et al, 2008;Wang et al, 2010;Su et al, 2015;Wu et al, 2015). Numerous studies likewise found that increasing contents of various metals, including Cu, Pb, and Zn, could be closely linked to mining and metalworking activities, reflecting a progressive intensification of human activities (Zong et al, 2010;Hu et al, 2013;Hillman et al, 2014;Wan et al, 2015;Xu et al, 2017;Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore essential to understand climate and human activities, as well as their impacts upon terrestrial ecosystems on longer timescales, in order to reconstruct each of them accurately. However, previous studies to determine human-environment interactions were mainly dependent on sediment cores from lakes (Dearing et al, 2008;Hillman et al, 2014;Su et al, 2015) and river deltas (Wang et al, 2010;Zong et al, 2010;Strong et al, 2013). Highresolution records from continental shelves are relatively scarce.…”
Section: Introductionmentioning
confidence: 99%